Nanoporous Carbon Prepared with MOF-5 as a Template and Activated using KOH for Hydrogen Storage - Ratna Ediati; Tri Ana Mulyati; Amirul Mukminin; Dety Oktavia Sulistiono; Naimatul Khoiroh; Hamzah Fansuri; Didik Prasetyoko (Jurnal Kimia Valensi, 2020)
A series of nanoporous carbon was prepared with MOF-5 as a template and furfuryl alcohol as an additional carbon source by carbonation at temperatures of 550 °C and 900 °C, respectively, with and without activation using KOH. XRD patterns of the obtained carbons before and after the activation process showed characteristic peaks at the same 2θ values, which corresponded to the XRD pattern of a ZnO. The Surface morphology of the MOF-5 templated carbon with a carbonation temperature of 550 °C was in the form of a cube. In contrast, the one carbonated at 900 °C had a cubic and circular morphology. The N2 adsorption-desorption isothermal showed that MOF-5 templated carbon had a larger specific surface area, pore diameter, and pore volume than those of the original MOF-5. Activation of the MOF-5 templated carbon using KOH resulted in a decrease in surface area and pore volume. All the materials were measured for their hydrogen adsorption at room temperature and atmospheric pressure using a gravimetric method.